Model Teori Fraud Diamond Mempengaruhi Financial Statement Fraud di Moderasi oleh Innovation Strategy - Angelina, Viona; Chandra, Budi (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
This study aims to examine the effect of fraud diamond on financial statement fraud and the role of innovation strategy in moderating the effect of fraud diamond on financial statement fraud. The research was conducted on companies listed on the Indonesia Stock Exchange using purposive sampling technique, while the analytical tools used were logistic regression analysis and moderating regression analysis. Samples were obtained from 89 companies registered from 2017-2021. The results showed that the component of the fraud diamond had a significant effect only on the DER variable, while the results of the study proved that the innovation strategy moderated the effect of the fraud diamond on the financial statement fraud.